Contested creations in the Book of Job : the-world-as-it-ought-and-ought-not-to-be - Pelham, Abigail. (Biblical Interpretation Series, 2012)
In Contested Creations in the Book of Job: the-world-as-it-ought- and -ought-not-to-be Abigail Pelham reads the Book of Job both 'forwards'-examining the perspectives on creation presented by Job and his friends and corrected by God's authoritative voice from the whirlwind-and 'backwards,' demonstrating how the epilogue explodes readers' certainties, forcing a reappraisal of the characters' claims. The epilogue, Pelham argues, changes the book from one containing answers about creation to one which poses questions: What does it mean to make the world? Who has the power to create? If humans have creative power, is it divinely sanctioned, or has Job, acting creatively, set himself up as God's rival? Engaging more thoroughly with Job's ambiguity than previous scholars have done, Contested Creations explores the possibilities raised by these questions and considers their implications both within the book and beyond.